Regulasi Tegangan Arus Searah Turbin Angin dan Baterai untuk Microgrid - Sidiq Budi Perkasa; Mochammad Facta; Iwan Setiawan (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2024)
Renewable energy will eventually replace fossil energy. Direct current (dc) microgrids can operate independently without being connected to the utility grid. The configuration of a dc microgrid system may encompass wind turbines, permanent magnet synchronous generators (PMSG), rectifiers, dc-dc boost converters, bidirectional dc-dc converters, batteries, and maximum power point tracking (MPPT). Systems with complex components have the problem of maintaining a stable dc voltage amid a load or wind speed change. This paper focuses on improving the performance of dc microgrids by adding voltage control to satisfy the load demand and maintain a constant dc voltage stability. Tests were conducted under three conditions. In the first condition, the wind turbine may supply the load and battery; in the second condition, the wind turbine and battery supply the load; and in the third condition, the battery fully supplies the load. The test results showed that the performance of the designed system could satisfy the load demand and charge the battery. When the wind turbine generators were unable to satisfy the load demand, the battery and wind turbine could supply the load. The system could maintain a voltage on the dc bus of 400 V, with a deviation of only 1%. According to the IEC 61000-14-17, this value remains within the acceptable load tolerance limit.